Review of Diseases in Which Occupational Cause is Likely in Medical Practice (Journal of Biomedical Investigation, 2009)
Whatever a medical doctor’s specialty, he or she may come across diseases related to occupation. The commonest of such diseases seen by the general practitioner are stress reactions. The orthopaedic surgeon is seen by patients with complaint of symptoms of over use syndromes, in the limbs and also back and waist problems. People who work with vibrating tools may come down with Raynaud’s syndrome and need to consult general surgeons. Workers in noisy work places may suffer noise induced hearing loss, or deafness or other symptoms like tinitus. All these people need the expert care of E.N.T (Ear, Nose and throat) surgeons. Females whose work exposes them to chemicals may suffer gynarcologic and endocrine reproductive problems many of such women suffer from infertility and need treatment by gynaecologists before they can have children. Dusty work places make workers come down with occupational lung diseases, and need treatment in respiratory medicine clinics. Some chemicals, encountered in some work environment cause renal and bladder problems. These conditions may need to be treated by internal physicians or even surgeons with bias for urology. There are also many non-specific symptoms that maybe related to the work place. The diagnosis of the above conditions depends on the medical doctor being alert to the possibility of an occupational cause and being able to take an appropriate occupational history.
Keywords: Review; Occupational; Diseases; Medical Practice